Os memes da Internet e a Cultura Visual Contemporânea como elementos pedagógicos na educação do Ensino Médio - Silva, Iram Leandro da (2025)
The rise of memes as a form of digital communication reflects a significant shift in how content is created, shared, and interpreted, especially among young people. This research contextualizes memes within contemporary visual culture, highlighting their relevance as digital artifacts that can foster new forms of engagement and learning within the educational environment. The primary aim of this study is to investigate the regimes of visuality operated by internet memes, which, in their visual constitution, contain content that contributes to the teaching and learning processes in high school. Specifically, this study seeks to analyze memes, discuss the intersections of humor, difference, and heteronormativity from the perspective of visual culture, understand how memetic discourses can enrich teaching and learning, and critically examine the field of images through Foucault's reflections on the microphysics of power. Adopting a qualitative-quantitative approach, the study employed questionnaires directed at teachers from the selected institution. The research was structured to capture the complexity of meme usage in educational contexts, addressing both the frequency and types of memes used and teachers' perceptions of their pedagogical effectiveness and associated challenges. The results demonstrate that memes, when integrated purposefully and with clear pedagogical objectives, play a significant role in engaging high school students and fostering knowledge construction. The analysis of the questionnaires administered to teachers revealed that using memes in educational practices not only captures students' attention but also facilitates initial comprehension of concepts, especially those of an abstract or complex nature. It was observed that memes, utilizing humor, irony, and contemporary cultural references, promote a more dynamic and collaborative learning environment in which students feel comfortable discussing and sharing their interpretations. Furthermore, the research identified that memes can be particularly useful in addressing issues of identity, diversity, and power, as they frequently contain implicit social and cultural commentary.